Epigenetics of Atherosclerosis: Emerging Mechanisms and Methods. Issue 4 (April 2017) - Khyzha, Nadiya; Alizada, Azad; Wilson, Michael D.; Fish, Jason E.
Abstract : Atherosclerosis is a vascular pathology characterized by inflammation and plaque build-up within arterial vessel walls. Vessel occlusion, often occurring after plaque rupture, can result in myocardial and cerebral infarction. Epigenetic changes are increasingly being associated with atherosclerosis and are of interest from both therapeutic and biomarker perspectives. Emerging genomic approaches that profile DNA methylation, chromatin accessibility, post-translational histone modifications, transcription factor binding, and RNA expression in low or single cell populations are poised to enhance our spatiotemporal understanding of atherogenesis. Here, we review recent therapeutically relevant epigenetic discoveries and emerging technologies that may generate new opportunities for atherosclerosis research. Trends: Recent studies have implicated epigenetic regulation in the etiology of atherosclerosis, but how epigenetic pathways are altered in specific cell types in the complex milieu of the plaque is not known. Emerging genomic technologies are circumventing the issue of limited material and can be used to resolve the epigenome in atherosclerosis at a single cell level. Epigenetic changes in atherosclerosis models as well as systems genetics approaches are providing insight into the effect of human genetic variations on atherosclerotic disease, especially variation within noncoding regions of the genome. Drugs that modify epigenetic pathways (e.g., DNA methylation, histone acetylation/methylation, and enhancer regulation) have shown promise in preclinical models of atherosclerotic disease. A further understanding of epigenetic mechanisms will open new avenues for treatment.